Laporan Kasus : Pasien Wanita 49 tahun dengan Proptosis et causa Thyroid Eye Disease Okuli Sinistra - Salsabilah, Nadya; Maulana, Muhammad (Medula, 2026)
Thyroid Eye Disease (TED), also known as Graves’ ophthalmopathy, is an extra-thyroidal manifestation of autoimmune thyroid disorders characterized by chronic inflammation of the orbital tissues. This condition may result in various ocular manifestations, including proptosis, diplopia, dry eyes, photophobia, and decreased visual acuity, significantly affecting patients’ quality of life. The development and progression of TED are influenced by both non-modifiable factors such as age, sex, and genetic predisposition, as well as modifiable factors including uncontrolled thyroid dysfunction, smoking, radioiodine therapy, oxidative stress, elevated TSH receptor antibody levels, and dyslipidemia. This case report describes a 49-year-old woman who presented with a protruding left eye for approximately five years prior to hospital admission. The patient also complained of blurred vision, diplopia, glare, and dry eyes. She had a history of hyperthyroidism diagnosed eight years earlier. Ophthalmologic examination revealed a left visual acuity of 2/20, upper eyelid retraction, and exotropia. Laboratory evaluation demonstrated elevated free thyroxine (T4) levels of 215.53 nmol/L and suppressed thyroid-stimulating hormone (TSHS) levels of <0.005 uIU/mL, consistent with hyperthyroid status. Based on clinical presentation and supporting investigations, the patient was diagnosed with proptosis due to Thyroid Eye Disease in the left eye. This case highlights the importance of early diagnosis, comprehensive assessment, and appropriate management of TED. Timely identification and control of modifiable risk factors, along with individualized therapeutic strategies according to disease severity, are essential to prevent disease progression, minimize complications, and preserve visual function and overall quality of life in patients with Thyroid Eye Disease.